Efficacy of neem and basil leaf extracts in controlling whitefly (Bemisia Tabaci) infestations and enhancing yield in curly red chili peppers (Capsicum annuum L.) - Diputra, Moses Graciano; Setiawan, Andree Wijaya (Universitas Lancang Kuning, 2024)
Whiteflies (Bemisia tabaci) are a major pest of curly red chili peppers, acting as vectors for gemini viruses that significantly reduce crop productivity. This study evaluated the efficacy of neem and basil leaf extracts at three different concentrations for controlling whitefly infestations on chili plants. A randomized complete block design (RCBD) was employed with 8 treatments and 2 controls: PA (Neem 1%), PB (Neem 2%), PC (Neem 3%), PD (Basil 1%), PE (Basil 2%), PF (Basil 3%), PKM (commercial pesticide as positive control), and P0 (distilled water as negative control). Parameters assessed included whitefly infestation intensity, yellowing of shoots, fruit weight, total fruit count, and the number of infested fruits. The results indicate that both neem and basil leaf extracts effectively reduced whitefly infestation intensity and yellowing of shoots compared to the negative control (P0). Despite some increase in infestation intensity in subsequent observations, both neem and basil extracts positively impacted fruit yield, including higher fruit weight and total fruit count. However, there was no significant effect on the number of infested fruits with the treatments. These findings suggest that neem and basil leaf extracts are promising alternatives for managing whitefly infestations and improving yield in curly red chili peppers.